Inconceivable Hypokalemia: A Case Report of Acute Severe Barium Chloride Poisoning - Haibo Tao; Yanru Man; Xiaoyuan Shi; Jun Zhu; Hang Pan; Qin Qin; Shanrong Liu (Case Reports in Medicine)
Barium is a heavy divalent alkaline earth metal that has been known as a muscle poison. Barium can cause human toxicity, which may lead to significant hypokalemia and have serious consequences. This paper reports a case of unprecedented barium intoxication in which the patient, who suffered from depression, swallowed at least 3.0 g barium chloride to commit suicide. On admission, the patient presented with nausea, vomiting, stomach burning feeling, dizziness, and weakness. Emergency biochemical testing showed that the patient was suffering from severe hypokalemia (K+ 1.7 mmol/L). His electrocardiogram (ECG) prompted atrioventricular blocking, ventricular tachycardia, prolongation of PR interval, ST segment depression with U waves, and T wave inversion. Intravenous potassium supplements were given immediately to correct hypokalemia and regular monitoring of vital signs and fluid balance was arranged. After all-out rescue of our hospital personnel, the condition of the patient is currently stable and he is gradually recovering. This case exemplifies the weaknesses of the management of toxic substances and the lack of mental health education for young people. We hope to get more attention for the supervision of toxic substances and the healthy development of young people.